Aplikasi Pencarian Produk Jual Mobile Devices dari Berbagai Situs E-commerce - Robby Christianto Wijaya; Justinus Andjarwirawan; Henry Novianus Palit (Jurnal Infra, 2016)
E-commerce sites in Indonesia offers many products with different prices. Consumers will find it hard to do a comparison of products by opening many existing e-commerce web. Therefore, a website portal is created for consumers to find and do a comparison of product from any existing e-commerce.The research focused on the feature for comparison between e-commerce products. Product comparison feature requires the server can retrieve product data from any e-commerce site and GSMArena. Then, process followed by parsing and processing on any e-commerce product data which has been established to be adapted to the product GSMArena.Based on the research, the time to get data e-commerce products and GSMArena products relies on the server's bandwidth and response time provided by each site. Products on each e-commerce have different product name from GSMArena, so the calculations is needed for the suitability of the product name between e-commerce and GSMArena.